Makna ‘Seneng lan Kemringet’ dalam Festival Lima Gunung - Joko Aswoyo; Rustopo Rustopo; Lono Lastoro Simatupang; Drajat Tri Kartono (PANGGUNG, 2018)
AbstractThis article aims to discover the meaning of the expression ‘seneng lan kemringet’ at FLG (Festival Lima Gunung) in Magelang. The expression ‘seneng lan kemringet’ gives an opportunity to anybody who involved to reveal his existence and to speak about the essence of himself. By building a sense of familiarity, direct involvement in art activities, and dialogue with the farmers about circumstances in the field, it will be possible to reveal the meaning behind the expression ‘seneng lan kemringet'. The research results showed that within the expression 'seneng lan kemringet', there is vitality as a fundamental asset for the FLG sustainability. ‘Seneng lan kemringet’ can also be understood as an autonomy and self-actualization. Additionally, 'seneng lan kemringet' is a part of a game with the goal of displaying self-existence. Finally, ‘seneng lan kemringet’ is an embodiment of self-esteem. Keywords: ‘seneng lan kemringet’, vitality, and game AbstrakArtikel ini bertujuan untuk mengetahui makna ungkapan ‘seneng lan kemringet’ pada Festival Lima Gunung (FLG) di Magelang. Ungkapan ‘seneng lan kemringet’ memberi kesempatan bagi yang terlibat untuk mengungkapkan keberadaannya dan berbicara tentang hakikat dirinya. Dengan keakraban, keterlibatan langsung dalam aktivitas kesenian, dan berdialog dengan petani atas kenyataan-kenyataan di lapangan, akan dapat disingkap makna di balik ungkapan ‘seneng lan kemringet’ tersebut. Hasil dari penelitian kami menunjukkan bahwa di dalam ungkapan ‘seneng lan kemringet’ tersimpan daya hidup sebagai modal dasar keberlanjutan FLG. ‘Seneng lan kemringet’ juga dimaknai sebagai otonomi dan aktualisasi diri. Selain itu, ‘seneng lan kemringet’ adalah bagian dari permainan dengan tujuan untuk memperlihatkan eksistensi diri. Pada akhirnya, ‘seneng lan kemringet’ merupakan kebanggaan diri.Kata kunci: ‘seneng lan kemringet’, daya hidup, dan permainan